2011
DOI: 10.1038/npp.2011.215
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Anatomical Thalamo-Cortical Connectivity and fMRI Activation in Schizophrenia

Abstract: The purpose of this study was to examine measures of anatomical connectivity between the thalamus and lateral prefrontal cortex (LPFC) in schizophrenia and to assess their functional implications. We measured thalamocortical connectivity with diffusion tensor imaging (DTI) and probabilistic tractography in 15 patients with schizophrenia and 22 age-and sex-matched controls. The relationship between thalamocortical connectivity and prefrontal cortical blood-oxygenation-level-dependent (BOLD) functional activity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
106
1
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 143 publications
(122 citation statements)
references
References 77 publications
13
106
1
2
Order By: Relevance
“…This is consistent with our previous observation that acute ketamine treatment enhances connectivity between the thalamic nuclei (Dawson et al, 2013). This contrasts with the thalamocortical dysconnectivity widely reported in schizophrenia, which is particularly evident in terms of PFC-thalamic dysconnectivity (Marenco et al, 2012;Welsh et al, 2010;Zhou et al, 2007;Woodward et al, 2012), although this is not always found (Klingner et al, 2013;Schlösser et al, 2003). In addition, there are examples of enhanced thalamic connectivity to other cortical subfields in schizophrenia, such as to motor and somatosensory areas (Woodward et al, 2012) and to the insular cortex (CorradiDell'Acqua et al, 2012).…”
Section: Discussionsupporting
confidence: 91%
“…This is consistent with our previous observation that acute ketamine treatment enhances connectivity between the thalamic nuclei (Dawson et al, 2013). This contrasts with the thalamocortical dysconnectivity widely reported in schizophrenia, which is particularly evident in terms of PFC-thalamic dysconnectivity (Marenco et al, 2012;Welsh et al, 2010;Zhou et al, 2007;Woodward et al, 2012), although this is not always found (Klingner et al, 2013;Schlösser et al, 2003). In addition, there are examples of enhanced thalamic connectivity to other cortical subfields in schizophrenia, such as to motor and somatosensory areas (Woodward et al, 2012) and to the insular cortex (CorradiDell'Acqua et al, 2012).…”
Section: Discussionsupporting
confidence: 91%
“…A meta-analysis of human imaging studies reported the left thalamus, dlPFC, and dACC to be activated significantly less in schizophrenia patients during cognitive tasks (Minzenberg et al, 2009). In addition, structural thalamocortical connectivity to the lateral prefrontal cortex was previously associated with WM performance (Marenco et al, 2012). In addition to the decreased thalamus-FPCN coupling, we also observed abnormally increased connectivity between the thalamus and parahippocampal gyrus in patients during task performance.…”
Section: Thalamus-fpcn Disconnection In Schizophrenia During Task Persupporting
confidence: 65%
“…The thalamus is connected to all cortical areas and conveys information to the neocortex, including information from the basal ganglia. Though a number of other studies have identified thalamic connectivity changes in the chronic stage of schizophrenia, 17,19,[22][23][24] such studies provide little information about early illness pathophysiology. In contrast, studies of FE schizophrenia have the advantage to specify brain changes at illness onset, thus providing crucial information about the pathogenesis of schizophrenia.…”
Section: Discussionmentioning
confidence: 99%
“…[17][18][19][20][21][22][23][24] Despite numerous leads, the reported findings are somewhat inconsistent and the core regions associated with the pathogenesis of schizophrenia still remain controversial.…”
Section: Introductionmentioning
confidence: 99%